2016
DOI: 10.22146/gamaijb.16899
|View full text |Cite
|
Sign up to set email alerts
|

Alliance Entrepreneurship and Entrepreneurial Orientation: The Mediating Effect of Knowledge Transfer

Abstract: Today's rapidly changing business environment has impelled companies to cooperate with their competitors in order to gain more competitive advantages through a win-win situation. Thereby, building alliances is one of the cooperative strategies that have been adopted by many enterprises, consequently attracting great attention from scholars. However, the literature about alliances seems to lack studies in the domain of entrepreneurship. Accordingly, this paper aims to extend entrepreneurship into the field of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study by Alvarez & Barney, 2001; Nakos et al, 2014 showed that most MSMEs conduct collaboration with large companies. The collaboration is among MSEs need to done because MSME tends to lack bargaining power in collaborative practices with large companies and will reduce the benefits of the collaboration [17]. Therefore, MSME should collaborate with fellow MSME because one of the factors driving the success of this collaboration is the similarity or linkage between MSMEs [2].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Alvarez & Barney, 2001; Nakos et al, 2014 showed that most MSMEs conduct collaboration with large companies. The collaboration is among MSEs need to done because MSME tends to lack bargaining power in collaborative practices with large companies and will reduce the benefits of the collaboration [17]. Therefore, MSME should collaborate with fellow MSME because one of the factors driving the success of this collaboration is the similarity or linkage between MSMEs [2].…”
Section: Introductionmentioning
confidence: 99%